2008
DOI: 10.21273/hortsci.43.7.2052
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Daily Light Integral during Propagation Influences Rooting and Growth of Cuttings and Subsequent Development of New Guinea Impatiens and Petunia

Abstract: A majority of commercial propagation of herbaceous ornamental cuttings occurs during the winter when the photosynthetic daily light integral (DLI) is relatively low. We quantified how the mean DLI influenced rooting and subsequent growth and development of two popular vegetatively propagated species, New Guinea impatiens (Impatiens hawkeri Bull.) and petunia (Petunia ×hybrida hort. Vilm.-Andr.). Three cultivars of each spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
85
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 14 publications
16
85
1
1
Order By: Relevance
“…For example, Hutchinson et al (2012) found that TTF for vegetatively propagated angelonia (Angelonia angustifolia) 'AngelMist White Cloud' and osteospermum (Osteospermum ecklonis) 'Voltage Yellow' was related linearly to the propagation DLI, with a greater DLI leading to earlier flowering at finish. Similarly, Lopez and Runkle (2008) found that TTF decreased for cuttings of petunia 'Tiny Tunia Violet' and 'Supertunia Mini Purple' as the propagation DLI increased from 1.4 to 10.7 mol · m -2 · d -1 . Species that flower earlier when grown under greater light environments exhibit a facultative irradiance response and generally develop fewer nodes before flowering as a result (Erwin et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, Hutchinson et al (2012) found that TTF for vegetatively propagated angelonia (Angelonia angustifolia) 'AngelMist White Cloud' and osteospermum (Osteospermum ecklonis) 'Voltage Yellow' was related linearly to the propagation DLI, with a greater DLI leading to earlier flowering at finish. Similarly, Lopez and Runkle (2008) found that TTF decreased for cuttings of petunia 'Tiny Tunia Violet' and 'Supertunia Mini Purple' as the propagation DLI increased from 1.4 to 10.7 mol · m -2 · d -1 . Species that flower earlier when grown under greater light environments exhibit a facultative irradiance response and generally develop fewer nodes before flowering as a result (Erwin et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…For impatiens, both HPS and LED SL during propagation decreased TTF compared with PL or natural light. Previous studies have shown that a greater propagation DLI generally decreases TTF for both seedlings and cuttings (Hutchinson et al, 2012;Lopez and Runkle, 2008;Oh et al, 2010). For example, Hutchinson et al (2012) found that TTF for vegetatively propagated angelonia (Angelonia angustifolia) 'AngelMist White Cloud' and osteospermum (Osteospermum ecklonis) 'Voltage Yellow' was related linearly to the propagation DLI, with a greater DLI leading to earlier flowering at finish.…”
Section: Discussionmentioning
confidence: 98%
“…However, the three-dimensional cultivation techniques developed by the advanced greenhouse industry are insufficient, and the light intensities provided to plants by such methods are also insufficient. 28,29 Because the lower layer of a multi-layer cultivation frame is blanked by the upper layer, the average amount of sunlight of lower layer is less than that of upper layer. In fact, plants may be grown in vain as a result of various forms of sunlight radiation loss, such as reflection loss, transmission loss, and penetration loss, which can make plants unable to achieve maximum photosynthetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The rate at which callus and adventitious root (AR) initials develop is temperature-dependent, thereby effecting AR formation (ARF) in cuttings. In addition, outdoor DLIs during late winter to early spring months are relatively low (5 to 20 mol · m -2 · d -1 ) compared with summer and fall months (30 to 50 mol · m -2 · d -1 ; Korczynski et al, 2002) and can be reduced by 50% or more from the greenhouse glazing material (Hanan, 1998) with further reductions from greenhouse infrastructure shading, white wash, and shade curtains (Lopez and Runkle, 2008). Although low DLIs (#5 mol · m -2 · d -1 ) during the early stages of propagation may be beneficial for minimizing stress and developing callus, excessively low DLIs (#2 mol · m -2 · d -1 ) can result in little to no ARF in cuttings.…”
mentioning
confidence: 99%
“…Previous research has investigated the effects of DLI and SL from high-pressure sodium (HPS) lamps and LEDs during AR development and subsequent rhizogenesis of numerous genera of vegetatively propagated annual bedding plants Hutchinson et al, 2012;Lopez and Runkle, 2008). In controlled environments, the effects of SSL provided by LEDs during seedling (plug) propagation (Randall and Lopez, 2015;Wollaeger and Runkle, 2015) and in vitro propagation (Budiarto, 2010;Gu et al, 2012;Jao et al, 2005) have been documented.…”
mentioning
confidence: 99%